Pharmacological incompatibility - A. I. Vengerovsky (Бюллетень сибирской медицины, 2003)
In the lecture there have been studied pharmacokinetic and pharmacodynamic mechanisms of drug undesirable interaction at combined pharmacotherapy and have been cited the urgent for general practitioner examples of pharmacological incompatibility.